Ableism, Racism, and Subminimum Wage in the United States - Friedman, Carli (Disability Studies Quarterly, 2019)
As subminimum wage is a prominent and problematic issue affecting the lives of many people with disabilities in United States, and as it is linked to discrimination, the aim of this study was to explore how prejudice impacts the use of special wage certificates and subminimum wage across the United States. Since in the United States employment discrimination has historically been tied to racism and sexism, in addition to ableism, we also were interested in exploring how those factors may impact the use of special wage certificates. To do so, we analyzed data about the use of special wage certificates around the United States, and prejudice data from 4.70 million people. Our findings revealed significant links between subminimum wage and not only ableism, but also racism. Subminimum wage practices are discriminatory and help normalize oppression.